Oral Health Status and The Body Mass Index in Young Adults - Rahmawan, Dzanuar; Kalanjati, Viskasari P; Abdurachman, Abdurachman (Folia Medica Indonesiana, 2020)
Poor oral health has been reported to correlate to the body mass index (BMI) of the overweight and the obesity groups. These has yet widely studied in Indonesia. The aim of this study was to analysed the oral health, socioeconomy factors (FSE) and the BMI in the seemingly healthy university students in Kediri aged 18-21 years old. This cross-sectional study was conducted amongst male and female students of IIKBW, Kediri, Indonesia (n=150). We analysed their BMI from the body weight and height (kg/m2). Their oral health was determined by the DMFT index (decayed missing filled teeth index), the stimulated salivary flow rate (SSFR) and the gingival index (GI). FSE studied include father's highest education and monthly income, tooth brushing frequency in a day and dental floss habitual use. Data was analysed using SPSS 17 with level of significance of p<0.05. No significant differences in BMI, DMFT index, SSFR and GI respectively (p=0.411;p=0.037, p=0.880, p=0.142) between male and female groups. No significant corelation BMI with DMFT index, SSFR and GI, respectively (p=0.340, p=0.420, p=0,446). FSE are not significantly correlated to either the BMI, DMFT index, SSFR orGI (p > 0.05). There were 41.8% of males and 57.8% of females have "bad” score of DMFT and 98.6% of males and 92.1% of females have "bad” score of GI; 4.1% of males and 2.6% of females have low score of SSFR.Although we found no significant differences in the BMI and oral health parameters between genders, in the seemingly healthy young adults oral health hygiene could be compromised as found in the current study indicated by bad scores of DMFT, SSFR or GI. Here we found that either BMI or FSE was not significantly correlated to any of oral health parameters measured in the current study.